Data Sources and Analytic Approaches Used to Evaluate the Impact of Patient and Public Involvement in Child Health Research: Simple Random Survey of Individual Studies in Published Reviews. - Miklaucic, Isabella; Borkhoff, Cornelia M.; Akbar, Sadia; Buchanan, Francine; Hattangadi, Nayantara; Giannarakos, Antonia; Law, Susan; Macarthur, Colin (Health Expectations, 2026)
Introduction: Several systematic and scoping reviews have focused on the impact of patient and public involvement (PPI) in child health research. The aim of this research was to examine the data sources and analytic approaches used by researchers to evaluate the impact of PPI in child health research. Methods: A comprehensive literature search identified published reviews focused on PPI impact in child health research. Titles, abstracts, and full texts were screened to determine eligibility. Individual studies from eligible reviews created the sampling frame, from which 100 individual studies were randomly selected. Information was extracted on primary study characteristics, type of PPI, data sources and analytic approaches used to evaluate PPI impact, and reported PPI impact. Frequency distributions were used to summarise the findings. Results: The initial search yielded 5868 citations. After screening, 15 reviews (comprising 406 individual studies, of which 303 were unique) met inclusion criteria. Among the 100 randomly selected individual studies, PPI was reported across all phases of the research process including priority setting (30/100), input on study materials (50/100), and dissemination of study findings (52/100). The method of PPI was most commonly focus groups (29/100) or advisory committees (27/100). Of the 100 studies selected, 67/100 reported impact on the research process, 69/100 reported impact on patients and families, and 32/100 studies reported impact on researchers. Regarding the data sources used to evaluate PPI impact, 69/100 studies reviewed primary study field notes along with researcher observations and reflections, while 31/100 studies conducted independent, specific, focus groups and/or interviews and/or surveys to gather data. Regarding the analytic approaches used to evaluate PPI impact, formal qualitative and/or quantitative analyses of the data occurred in only 25/100 studies. Only 2/100 studies used a formal PPI reporting guideline. Conclusion: Only 31/100 studies collected specific, independent data on the impact of PPI in child health research, and only 25/100 studies applied formal analyses. Robust evaluation of PPI impact in child health research is essential for a strong PPI evidence base. Patient or Public Contribution: A patient partner (co‐author, FB) was a member of the research team from study inception, and contributed to the development of the study protocol, including refining the research question, input on study design, selection of relevant outcomes, interpretation of findings, writing the manuscript, and developing dissemination plans.